2015
DOI: 10.1186/s13287-015-0188-9
|View full text |Cite
|
Sign up to set email alerts
|

Association between in vivo bone formation and ex vivo migratory capacity of human bone marrow stromal cells

Abstract: IntroductionThere is a clinical need for developing systemic transplantation protocols for use of human skeletal stem cells (also known bone marrow stromal stem cells) (hBMSC) in tissue regeneration. In systemic transplantation studies, only a limited number of hBMSC home to injured tissues suggesting that only a subpopulation of hBMSC possesses “homing” capacity. Thus, we tested the hypothesis that a subpopulation of hBMSC defined by ability to form heterotopic bone in vivo, is capable of homing to injured bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 50 publications
1
10
0
Order By: Relevance
“…IL-1β and TNF-α are the primary cytokines for inflammation and matrix degradation ( 8 , 13 , 20 , 25 ). Therefore, the present study also assessed the concentration of IL-1β and TNF-α in PCP and P-PRP obtained using different conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IL-1β and TNF-α are the primary cytokines for inflammation and matrix degradation ( 8 , 13 , 20 , 25 ). Therefore, the present study also assessed the concentration of IL-1β and TNF-α in PCP and P-PRP obtained using different conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The results demonstrated that P-PRP obtained using the optimal conditions significantly promoted the proliferation and migration of hBMSCs and hACs compared with P-PRP obtained using other conditions. Numerous studies have demonstrated that the promotion of proliferation and migration of hBMSCs is beneficial for the regeneration of bone ( 25 ) and cartilage ( 32 ) and that the promotion of proliferation and migration of hACs is beneficial for the treatment of arthritis ( 33 ). Therefore, P-PRP obtained using the optimal conditions identified may also be more effective in the treatment of bone defects, osteochondral defects and arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…However, the findings of the present study suggest that only a limited number of BMSCs used in systemic transplantations possess homing capacity toward injured tissue. A molecular signature that defines this population has been identified, and a surface marker PDGFRβ can be employed for potential isolation of the BMSCs with enhanced migratory capacity 87. Recent data also demonstrate functional association between in vivo bone forming ability and homing capacity of BMSCs.…”
Section: Migration Of Mscs To the Site Of Injurymentioning
confidence: 99%
“…Our results demonstrated that PRP prepared from harvested blood and venous blood had similar effects on promoting proliferation and enhancing viability of HBMSCs. It is universally known that HBMSCs proliferation and viability are beneficial for tissue regeneration in bone or osteochondral lesions [ 29 , 30 ]. Therefore, PRP prepared from harvested blood and venous blood may have similar outcomes in spinal fusion.…”
Section: Discussionmentioning
confidence: 99%